CURRENT STATE OF POSTOPERATIVE RADIOTHERAPY OF LUNG CANCER - Yu. A. Ragulin (Сибирский онкологический журнал, 2016)
The problem adjuvant treatment of non-small cell lung cancer there are many unresolved questions, postoperative radiation therapy (PORT) is more controversial. Over the last decade there have been significant changes in the assessment of treatment results and treatment indications. Improvements in diagnostics of preoperative staging and the use of modern radiological technics improve survival in patients with resectable non-small cell lung cancer with mediastinal lymph nodes metastasis. This article presents the results of the most significant studies PORT with the modern technologies of diagnostics and treatment. Ongoing randomized trials will provide new data on the effectiveness of PORT.